The impact of blended learning models on enhancing students’ confidence and stability in foreign language education - Alqahtani, Suad Mohammad Saeed; Koka, Nisar Ahmad; Ahmad, Javed; Jan, Nusrat; Khasawneh, Mohamad Ahmad Saleem (Research Journal in Advanced Humanities, 2025)
This study focuses on a multitude of variables, encompassing learners' engagement, self-determination, technological tools, and instructors’ intervention or support, that collectively impact students' confidence and resilience in the context of foreign language education. Furthermore, ninety–seven (97) research individuals who served as research participants were engaged in an online survey to share their opinions on the efficacy of the use of blended learning models. Their responses which form the basis of the research data were presented and analyzed. Moreover, these responses further answered the two basic research hypotheses, which try to validate the extent to which blended learning models can impact language learners’ confidence on one hand, and on the other hand, ensure that they have stability during their language learning acquisition. The findings of the research highlighted engagement, digital tools, motivation, and language instructors’ support as basic factors associated with the blended learning models. The findings also explored the effective integration of blended learning approaches in language learning settings, facilitates students’ language acquisition, boosting the learners’ confidence and further creating a conducive environment for a smooth learning experience. The research, however, recommends constant utilization of this pedagogical method to effectively harness its benefits and provide language learners with constructive feedback to aid in facilitating their language acquisition.